Crystal growth and nucleation kinetics of diethylenetriammonium hexachlororhodate (III) salt - Engelbrecht,Edmund (Department of Chemical Engineering, 2022)
At Anglo American Platinum's Precious Metal Refinery, rhodium separates from a base metal-rich solution by precipitation. Hexachlororhodate (III) ions and cationic protonated diethylenetriamine ions exchange to form diethylenetriammonium hexachlororhodate (III) crystals, a rhodium metal precursor. The objective of this work is to determine nucleation and growth kinetics of diethylenetriammonium hexachlororhodate (III) salt. Two reactor configurations, namely a transient continuous stirred tank reactor (CSTR) and a t-mixer plug flow reactor (PFR), were used to determine nucleation and growth rates. The objective of the configurations was to eliminate kinetic biases that may be caused by mixing at the mesoscale. Transient saturation in the CSTR ranged up to 43, and in the PFR saturation was varied between 2 and 64. Precipitation kinetic parameters were estimated through data fitting concentration and volume average crystal size profiles to a mass and population balance model. Temperature dependence of kinetic parameters was found to be universal between reactor configurations. Both growth through interfacial attachment and agglomeration, as defined in this work, were exothermic processes with activation energies of -192.9kJ/mol and -656.1kJ/mol respectively. Nucleation was found to be an endothermic process with an activation energy of 50.9kJ/mol in accord with the observed heat of crystallisation. No evidence of heterogeneous primary nucleation in the form of crystals adhering to the side walls of the reactor or the agitator blades was observed. The experiments were not explicitly designed to distinguish between primary and secondary nucleation mechanisms, therefore excluding one over the other is not justified. However, considering the presence of nucleated crystals in each system combined with the good model fit using a nucleation rate expression typically associated with secondary nucleation, it is likely that the dominating nucleation mechanism is secondary in nature. In the PFR configuration, nucleation and growth occur at a faster rate compared to the CSTR under the experimental conditions in this work. This observation is inferred from the fitted temperature independent kinetic parameters and is linked to a much higher mixing intensity achieved in the PFR relative to the CSTR. Flow conditions, described by the Reynolds number, can limit conversion in the PFR configuration by a mixing limitation at the micro- or mesoscale. Micro- and mesoscale mixing were represented by a characteristic length scale that was empirically related to temperature for the microscale and fluid velocity for the mesoscale. Under conditions where the Reynolds number is below the point where conversion is independent of the Reynolds number, either micromixing or mesomixing can become a rate limitation. At a sufficiently high Reynolds number neither micromixing nor mesomixing limits conversion and the system equilibrium becomes the limitation. In the CSTR, the system equilibrium limited reaction conversion as the micro- and mesoscale mixing zones were sufficiently small relative to the reactor volume. Parameters related to mixing were found to differ between the configurations, which was caused by different flow patterns within each configuration. Scanning electron microscopy (SEM) photographs suggest that crystals in the PFR configuration collide both in the radial and axial direction, giving rise to a feathery flat and elongated agglomerated crystal cluster. In contrast, the crystals in the CSTR configuration collide in a chaotic but consistent pattern, giving rise to a desert rose-like agglomerated crystal cluster. The derived model used to describe agglomeration is based on the agglomeration principles proposed by Von Smoluchowski coupled with Fick's law of diffusion and gives a good representation of crystal size. The PFR growth rate supersaturation exponent was 1.13, suggesting a Burton-Cabrera-Frank type growth model, and is indicative of crystal growth from screw dislocations that is limited either through mass transfer to the crystal surface, or surface integration. Thus, in this instance, the rate of aqueous hexachlororhodate (III) conversion to crystal would be responsive to mixing conditions on the micro- or mesoscale, as was experimentally found in the PFR configuration. In comparison, the CSTR growth rate supersaturation exponent was 2.31 and is more in line with polynuclear growth that appears to be limited by interfacial attachment kinetics, as the system equilibrates in the bulk. Lastly, a key finding of this work is the ability to manipulate the crystal morphology by changing reactor configuration. By creating elongated flat crystal structures in the PFR configuration as opposed to a desert rose crystal structure in the CSTR, it may be possible to reduce impurities within the crystal by entraining less mother liquor.